Operational strategies for an activated sludge process in conjunction with ozone oxidation for zero excess sludge production during winter season - Lee, JW; Cha, HY; Park, KY; Song, KG; Ahn, KH (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
A pilot-scale activated sludge system coupled with sludge ozonation process was operated for 112 days of a winter season without excess sludge wasting. The concept of this process is that the excess sludge produced is first disintegrated by ozone oxidation and then recirculated to a bioreactor in order to mineralize the particulate and soluble organic compounds. The basis of operation was to determine either the optimal amount of sludge in kg SS ozonated each day (SO) or the optimal ozonation frequency under the variable influent chemical oxygen demand (COD) loading and temperature conditions, since the ozone supply consumes costly energy. The optimal SO was obtained using the theoretically estimated sludge production rate (SP) and experimentally obtained ozonation frequency (n). While the SP was mainly subject to the COD loadings, sludge concentration was affected by the temperature changes in winter season. The optimal n was observed between 2.5 and 2.7 at around 15 degrees C, but it was doubled at 10 degrees C. Mixed liquor suspended solids (MLSS) concentration was leveled off at around 5000 mg/L in bioreactor at 15 degrees C, but the volatile fraction of MLSS was fixed around 0.7 indicating that there was no significant inorganic accumulation. Suspended solids (SS) and soluble COD in effluents kept always a satisfactory level of 10 and 15 mg/L with sufficient biodegradation. It was recommended to apply a dynamic SO under variable influent COD loadings and temperature conditions to the activated sludge system without excess sludge production for saving energy as well as system stabilization. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: ANAEROBIC-DIGESTION; SEWAGE-SLUDGE; OZONATION; STABILIZATION; REDUCTION